2012
DOI: 10.1146/annurev-neuro-062111-150444
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Gamma Oscillations

Abstract: Gamma rhythms are commonly observed in many brain regions during both waking and sleep states, yet their functions and mechanisms remain a matter of debate. Here we review the cellular and synaptic mechanisms underlying gamma oscillations and outline empirical questions and controversial conceptual issues. Our main points are as follows: First, gamma-band rhythmogenesis is inextricably tied to perisomatic inhibition. Second, gamma oscillations are short-lived and typically emerge from the coordinated interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

111
2,110
3
18

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,367 publications
(2,337 citation statements)
references
References 160 publications
111
2,110
3
18
Order By: Relevance
“…Contrary to the null result previously reported, we found that pharmacological enhancement of GABAergic neurotransmission by tiagabine produced a marked decrease in the peak frequency of visual gamma oscillations. The result supports the authors' original predictions [Muthukumaraswamy et al, 2013a], and provides additional translational evidence for the neurophysiological mechanisms generating gamma oscillations in humans [Bartos et al, 2007; Buzsáki and Wang, 2012]. …”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Contrary to the null result previously reported, we found that pharmacological enhancement of GABAergic neurotransmission by tiagabine produced a marked decrease in the peak frequency of visual gamma oscillations. The result supports the authors' original predictions [Muthukumaraswamy et al, 2013a], and provides additional translational evidence for the neurophysiological mechanisms generating gamma oscillations in humans [Bartos et al, 2007; Buzsáki and Wang, 2012]. …”
Section: Introductionsupporting
confidence: 86%
“…In relatively simple models, the generative mechanisms of gamma oscillations consist of pyramidal cells firing synchronously under the inhibitory control of GABAergic interneurons [see Bartos et al, 2007; Buzsáki and Wang, 2012; Gonzalez‐Burgos and Lewis, 2012; Tiesinga and Sejnowski, 2009, for reviews]. At the synaptic level, tiagabine exerts its effects by selectively inhibiting GAT‐1, the most abundantly expressed GABA transporter (GAT) in the cerebral cortex [Borden et al, 1994; Conti et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because electric fields propagate in the brain, LFP recordings may also reflect propagated signals from nearby sources, a process that is known as volume conduction, which is particularly relevant when strong generators for the observed oscillatory phenomena are known to exist. Convergent evidence suggests that higher frequency oscillations in the beta and gamma range tend to reflect local synchronized firing and are not passively propagated over large distances (Steriade and Amzica, 1996;Buzsáki and Wang, 2012;Welle and Contreras, 2016). Low frequency LFP modulations in delta, theta and alpha bands however need to be interpreted with particular caution, given the robust, large amplitude, and highly synchronized theta oscillations that are present in the hippocampus that have been shown to affect cortical LFP recordings particularly in the rat where these structures are in close proximity (Buzsáki, 2002;Sirota et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…17,52,53 It is also in line with the models of gamma oscillations in neuronal networks that emphasize the importance of rhythmic and synchronous inhibition of both pyramidal cells and interneurons, which finally generates alternating phases of enhanced or decreased probability of spiking. 9,54 Initial models argued that the cycle of gamma oscillations (B25 ms for 40 Hz) is dominated by the duration of slow IPSPs. Subsequent direct electrophysiological measurements revealed faster kinetics of IPSPs than compatible with the gamma cycle.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%